PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) MELALUI TEKS DRAMA “SULTAN SURIANSYAH” - Noortyani, Rusma; Maghfirah, Alfanida; Maryaeni, Maryaeni; Mu'in, Fatchul (Jurnal Pembelajaran Sastra, 2022)
This study aims to describe the implementation of learning literature to students in class 8C at SMPN 21 Banjarmasin, South Kalimantan, applying the Culturally Responsive Teaching (CRT) approach to the drama text "Sultan Suriansyah". This study uses a qualitative method that produces descriptive data in the form of speech or writing and observes behavior of students. The results showed that learning begins with orientation, apperception, motivation, and giving references. Furthermore, the core activities carried out by educators through the CRT approach are self-identification, culturally understanding, collaboration, critical reflection, and transformative construction. The last part of the learning activities carried out by educators is in the form of reflection and follow-up plans. The assessment carried out is the cognitive assessment of students obtained from assignments in the form of text. Indicators for achieving competency 3.15.1 in the form of analyzing the intrinsic elements of the drama presented have been completed with a percentage of 96.7%. Indicators for achieving competency 3.15.2 in the form of analyzing the interrelationships between elements of the drama presented have been completed with a percentage of 60%. The affective value, in the form of self-confidence shows that the level of self-confidence of students has developed as expected, it is 93.4%. The attitude of responsibility shows that the level of responsibility of 56% of students has developed according to expectations and 43.3% has greatly developed. The attitude of cooperation shows that the level of cooperation of 66.7% of students has developed according to expectations and 33.3% has greatly developed. The psychomotor value, namely the ability to discuss students shows that 63.3% of students have achieved the minimum completeness criterion value. Likewise, the presentation skills of students showing 70% of students have achieved the minimum completeness criterion score of 70.